Злочинність в установах виконання покарань: основні детермінанти - Журавська, З.; Батюк, О.; Zhuravska, Z.; Batyuk, O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено проблеми визначення причин злочинності в місцях позбавлення волі, проаналізовано питання діяльності установ виконання покарань. Вивчено та розглянуто основні детермінанти злочинності, поширені в місцях позбавлення волі. Зроблено висновок про те, що працівники УВП самі повинні бути досвідченими конфліктологами, мати необхідні знання, уміти згладжувати, локалізовувати конфлікти, які виникли й можуть призводити до вчинення злочинів.The article is devoted to the problems of determining the causes of crime in prison. It deals with the questions of penal institutions. The key determinants of crime that are common in prisons today are examined and discussed. Nowadays a considerable number of researchers work on the solution of the mentioned above problem, and in spite of the large number of findings connected with the issues of crime in the prison, there are still many unsolved problems. In this regard, we can make a conclusion that the places of executing punishment should become the subject of a comprehensive scientific research with no doubt and such investigation should be focused on the real needs of the practice. At the same time the staff the places of executing punishment must be experienced conflictologists as well as to have the necessary knowledge, to be able to smooth and localize developed conflicts that may lead to crime. The article also examines the issue of low-level crime prevention which is one of the major determinants of crime in prison.
Crime in Penal Institutions: the Main Determinants
Keywords: злочин; місця позбавлення волі; детермінанти злочинності; засуджений; crime; prisons; the determinants of crime; convicted